The chronicle of Ibn al-Athīr for the crusading period from al-Kāmil fīʼl-taʼrīkh. The Years 589-629/1193-1231: The Ayyubids after Saladin and the Mongol Menace / Part 3, ([2020?]) - Unknown
No abstract available